Smile dental journal
"Smile dental journal is quarterly issued, peer-reviewed open access journal. Subject coverage is dentistry, dealing with all specialties of dentistry, its management, besides dental health related subjects ... Bridging the gap between advanced up-to-date peer-reviewed dental literature and the dental practitioners"--Publisher's description.